Assesing the Impact of Financial Deepening on Income Inequality: The Case of Malaysia - Abd Jabbar, Jun Faredda (2008)
Malaysia is one of the fastest developing countries in Southeast Asia. Malaysia, throughout the years, have managed to become one of the more rapidly developing countries and managed to uphold its own during the recent 1997 Asian financial crisis. Considered as a middle-income country, Malaysia has committed itself to becoming a developed country by 2020. This is the cornerstone of the Ninth Malaysia Plan (2006–2010), which also targets the elimination of hardcore poverty and a reduction in overall poverty incidence by 50%. This national commitment follows the country’s strong economic performance with real gross domestic product (GDP) growing an average of 5.9% per year over the four years to 2006. Throughout the years, the Malaysian economy has benefited from strong growth in world consumer demand for electronic products. As a net petroleum exporter, high crude oil prices have also provided revenues that have helped mitigate the broad negative impacts of high energy prices. The Malaysian Government is focusing on policies and investment plans that support inclusive growth, with particular emphasis on addressing long-standing concerns about economic disparities between ethnic groups and regions. Reducing inequality is not only important from the point of view of achieving a more equal distribution of income and addressing the welfare and social concerns that the widening disparities in income can raise. Rising income inequality may also reflect a lack of economic opportunity, and it may itself exploit the new opportunities created by globalisation for Malaysia. One of the most important aspects of a developing nation is the level of income inequality of that particular nation as it is one of the indicators of the well being of the citizens of the country. One of the key developments of a country is to what extent is the level of financial deepening of that particular country. Financial development matters as the nation would have more access to credit markets, which will benefit the poor via public and domestic investments. With more access to credit the poor can invest in their own education and that of their future generations. They can then increase and improve their mobility and economic prospects and hence break the cycle of persistent income inequality. The objective of this paper is to specify and explain theoretically the determinants of financial deepening in Malaysia, and attempt to identify the effects of financial deepening on the income inequality in Malaysia from 1980 to 2000. The method of time series was employed in order to capture the effect of financial deepening in Malaysia on income inequality. I have adopted the income inequality measurement called the Gini coefficient developed by an Italian statistician named Gorrado Gini in the 1910’s and is commonly used to indicate the changes in Malaysia’s income inequality. The database for Malaysia is considered relatively good by developing country standards. The use of annual data covering the period 1980–2000 is sufficiently long to allow for a meaningful time series investigation, which addresses the concerns raised about the lack of time series-based individual country studies (Ang and Mckibbin, 2007). This paper will begin with the reviewing existing literatures and studies written by various authors, which will delve into the history of Malaysia’s financial deepening, and to briefly describe the determinants of financial deepening theoretically. Then this paper will look at different literature on the effect of financial deepening on income inequality. The next section will be the explanation of the data and methodology as well as the econometric model employed. The result obtained shall be discussed as well a brief comparison of different studies on the effect of financial deepening and income inequality will be provided.